The Cu/Zn superoxide dismutase +35A/C (rs2234694) variant correlates with altered levels of protein carbonyls and glutathione and associates with severity of COPD in a Tunisian population. (4th March 2019) - Ben Anes, Amel; Ben Nasr, Hela; Garrouche, Abdelhamid; Bchir, Sarra; Dhaouefi, Zaineb; Chabchoub, Elyes; Tabka, Zouhair; Chahed, Karim
Abstract: Chronic obstructive pulmonary disease (COPD) is a major cause of mortality that has been associated with inflammation and oxidative stress. The purpose of the present case–control study was to determine the relationships between oxidative stress-related genetic variants and the risk and severity of COPD, as well as, the influence of these variants on inflammatory and oxidative stress parameters. Genotyping of superoxide dismutase 1 (SOD1) + 35 A/C (rs2234694), catalase [A-21T (rs7943316), C-262T (rs1001179)] and glutathione peroxidase 1 (reduced glutathione (GSH)-Px1) 198Pro/Leu (rs1050450) was carried out in 143 patients with COPD and 216 healthy controls using PCR-RFLP. Serum levels of IL-6 and TNF-α were determined by enzyme-linked immunosorbent assays (ELISA), while the levels of reduced GSH, total antioxidant status (TAS), H2 O2, lipid peroxides (TBARS) and protein carbonyls (PCs) were determined using spectrophotometric methods. We also evaluated the activities of GSH-Px, catalase, and superoxide dismutase (SOD) in both plasma and erythrocytes. We did not observe significant differences in the genotype and allele frequencies of chosen variants between COPD patients and healthy controls. A significant correlation was retrieved between the SOD1 + 35A/C variant and disease severity (odds ratios (OR) = 0.15, p = 0.04). In addition, patients having the +35AC genotype presented increased plasma levels of GSH and a reduced level of PCs ( p = 0.03, p = 0.04, respectively). The present data highlighted the important role of antioxidant enzymes and their genetic variants in the oxidative stress-mediated pathogenesis and progression of COPD.